Nurse Managers' Experiences in Managing Inpatient Wards During a Crisis: Lessons from the COVID-19 Pandemic - Tombong, Andi Baso; Ilmi, Ani Auli (Media Kesehatan Masyarakat Indonesia, 2024)
The COVID-19 pandemic has provided valuable lessons for all parties, including nursing services in hospitals. To date, literature has been lacking on the role of nurse managers in managing inpatient wards for COVID-19 patients, especially in Indonesia. This study aims to explore the experiences of, and the challenges encountered by nurse managers in managing inpatient wards during the crisis. This is a qualitative study with a phenomenology design. The study used a purposive sampling technique involving four nurse managers from several hospitals in South Sulawesi Province, Indonesia. Data were obtained through semi-structured interviews and were analyzed using thematic analysis. This study yielded three themes and nine sub-themes. Nurse managers experienced panic and fear but carried out inpatient management immediately. There was also a solid commitment to protect the fellow nurses from infection. Valuable lessons include the availability of human resources, strong commitment from all lines, management support, and teamwork. Meanwhile, nurse managers encountered challenges such as the lack of personal protective equipment, frequently changing service procedures and the psychological needs of nurses. Nurse managers obtained numerous lessons from the COVID-19 pandemic related to their capabilities in managing inpatient wards. The findings suggest the adaptability of nurse managers to similar challenging crisis encounters in the future by analysing the effects of frequent workflow changes on care quality and staff adaptation, examining the long-term psychological impact of pandemic work on nurses developing strategies to enhance organizational support for nurses including coping mechanisms and well-being related trainings and services, and to build dynamics of effective teamwork during crisis.